Multi-criteria decision-making approach for building maintenance in facility management - Besiktepe, Deniz, author; Ozbek, Mehmet E., advisor; Atadero, Rebecca A., advisor; Grigg, Neil S., committee member; Bradley, Thomas H., committee member; Valdes-Vasquez, Rodolfo, committee member (Colorado State University. Libraries, 2021)
Facility Management (FM) encompasses multi-disciplinary processes to ensure the built environment functions properly for its intended use and service. Maintenance practices are critical to sustaining the longevity of the built environment. As buildings continue to age, there is an increasing need for effective maintenance practices and strategies. In addition, cost and financial constraints require enhanced processes in building maintenance decision-making to assure the resources are allocated efficiently to get the best possible outcome. Building maintenance decisions present challenges to FM professionals. These challenges arise from the complexity of building systems as well as the participation of multiple stakeholders in the process, such as the property owner, facility manager, engineer, project supervisors, technicians, and occupants. The overarching goal of this dissertation is to develop a systematic and structured multi-criteria decision-making (MCDM) approach for building maintenance practices in a resource-constrained environment. To do so, this dissertation includes three separate but related studies; each focusing on the essential pieces of the MCDM approach. The first study identified the set of fundamental criteria needed for constructing an MCDM model for FM decision-making utilizing the results of a nationwide survey conducted with the members of the International Facility Management Association (IFMA) and the Leadership in Educational Facilities (APPA) in the United States, two globally recognized FM organizations. The first study also has an exploratory aspect and tries to establish the decision-making and condition assessment practices currently used in FM practices. The second study focused on developing a resource-efficient and quantitative condition assessment (CA) framework to establish a condition rating value. Condition information is essential in the decision-making process of building maintenance; however, financial challenges limit the practice of CA, which currently is mostly based on visual inspections and likely to generate a subjective outcome. Fuzzy sets theory is utilized to obtain a quantitative condition rating value that would be less subjective than that obtained through visual inspections, as fuzzy sets theory deals with imprecise, uncertain, and ambiguous judgments with the membership relations. In the third study, an MCDM method, Choosing by Advantages (CBA), is used to develop a structured and systematic decision-making approach in building maintenance and FM. CBA allows the identification of the most-value generating alternative in the absence of cost and financial constraints, which helps to eliminate the dominancy of financial considerations in the decision-making process. In addition, CBA provides a practical framework to decision-makers in FM with various backgrounds, allowing the participation of multiple stakeholders in the process. This study contributes to the body of knowledge in the FM domain by identifying criteria in the building-maintenance decision-making process, developing a less subjective and quantitative CA framework, and demonstrating an MCDM method for a systematic approach in building-maintenance decision-making. Additionally, this study will benefit FM professionals and decision-makers at all levels by helping to prioritize maintenance activities, justify maintenance budget requests, and support strategic planning.
Keywords: choosing by advantages; facility management; multi-criteria decision-making; condition assessment; building maintenance; fuzzy sets theory